Bank cooperation and banking policy in a monetary union: A political-economy perspective on EMU - Hans Peter Grüner; Carsten Hefeker (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
Why do large European banks lobby for monetary union? We show in a game-theoretic model that monetary union can trigger a change in the structure of the market for international banking transactions with asymmetric effects on profits: large banks are induced to cooperate internationally and gain from European Monetaiy Union (EMU) while small banks are likely to lose. Monetary union can be interpreted as a device for large banks to push small banks out of the market for cross-border financial services.
Keywords: E5; F3; G2; 330; European Monetaiy Union; Interest Groups; Banking Policy; Bank Cooperation